Musculoskeletal Pain in Patients with Psoriasis and its Influence on Health-related Quality of Life: Results from a Danish Population-based Survey - Sara Kamp Felbo; Lene Terslev; Inge Juul Sørensen; Lone Skov; Claus Zachariae; Mikkel Østergaard (Medical Journals Sweden, 2021)
This study used a nationwide e-based survey of patients with psoriasis to assess the pattern of musculoskeletal pain and its influence on patient-reported outcomes, including health-related quality of life and disability. A total of 561 respondents (56% of the screened psoriasis patients) reported physician-diagnosed psoriasis and completed the questionnaire. Respondents were grouped based on the presence of musculoskeletal pain and/or diagnosed psoriatic arthritis: 81% had psoriasis without arthritis (29% pain now, 23% pain previously, 39% no pain ever), and 19% had psoriatic arthritis. Patients with psoriasis with pain now had poorer quality of life compared with patients without pain and, importantly, similar to that of patients with arthritis. Furthermore, patients with pain now/previously reported higher self-assessed severity of psoriasis and lower satisfaction with current treatment than patients without pain. Two-thirds of patients with psoriasis with pain now/previously and one-third of patients with arthritis had never been examined by a rheumatologist, demonstrating an unmet need for adequate evaluation of such patients. A nationwide e-based survey of patients with psoriasis was preformed to assess the pattern of musculoskeletal pain and its influence on patient-reported outcomes, including health-related quality of life and disability. A total of 561 respondents (56% of the screened psoriasis patients) reported physician- diagnosed psoriasis and completed the questionnaire. Respondents were grouped based on the presence of musculoskeletal pain and/or diagnosed psoriatic arthritis: 81% had psoriasis without arthritis (29% pain now, 23% pain previously, 39% no pain ever), and 19% had psoriatic arthritis. Patients with psoriasis with pain now had poorer quality of life compared with patients without pain and, importantly, similar to that of patients with arthritis. Furthermore, patients with pain now/previously reported higher self-assessed severity of psoriasis and lower satisfaction with current treatment than patients without pain. Two-thirds of patients with psoriasis with pain now/previously and one-third of patients with arthritis had never been examined by a rheumatologist, demonstrating an unmet need for adequate evaluation of such patients.